Os Odontoideum: A Single-Center Experience with Controversies in Management and Evolution of Treatment Strategies - Yerramneni, Vamsi Krishna; Sharma, Neeraj (Indian Journal of Neurosurgery, 2021)
Os odontoideum is an independent ossicle of variable size and shape separated from the body of C2. There are various theories on the etiology. Different hypothesis on etiology include traumatic and congenital. Because of the laxity of the ligaments associated with the anomalous odontoid, there can be associated instability at the craniovertebral junction. The authors presented their experience of treating these anomalies, their clinical presentations, evolution of the treatment strategies over years, and a brief review of literature on etiopathogenesis.
Keywords: os odontoideum; etiology; treatment options; controversies of management